Basic concepts in biology : - Starr, Cecie (Brooks Cole / Thomson Learning, 2003)
This best-selling text?a compilation of 32 chapters drawn from Cecie Starr's BIOLOGY: CONCEPTS AND APPLICATIONS, Fifth Edition?is designed to help students understand biology by engaging them in learning in every way possible. The book's extensive array of multimedia resources enriches the book's hallmark features: unique visuals on every page, applications in every chapter that show how biology is inextricably linked to everyday life, and activities and resources throughout the book that encourage critical thinking and spark curiosity in biological investigation.